In-depth exploration and application of fracturing construction curves in fractured tight sandstone reservoirs of the Tarim Basin - Cai, Mingjin; Zhang, Haofei; Qiang, Jianli; Wang, Zhimin; Yin, Guoqing; Xie, Chaoqun; Chen, Keyou; Xi, Haojiang (Frontiers in Earth Science, 2024)
Fractured tight sandstone reservoirs are representative reservoirs in the Tarim Basin, characterized by the development of natural fractures and diverse interaction modes between artificial and natural fractures. The complex shape of the construction pressure curves during fracturing makes it difficult for existing fracture extension diagnosis methods to provide effective guidance. To thoroughly explore the information contained in the construction curves and accurately characterize hydraulic fracturing parameters, this study proposes a dynamic bottomhole net pressure calculation method based on real-time fracturing construction data, allowing for more precise correction of the bottomhole net pressure. Subsequently, a fracture extension mode recognition mechanism for fractured tight sandstone reservoirs is established, identifying five modes of fracture extension: activation of natural fractures, restricted extension, complex fracture extension, communication with natural fractures, and vertical penetration of fractures. The concept of a post-fracturing complex fracture network index is introduced, leading to a comprehensive method for diagnosing and recognizing construction pressure curves suitable for fractured tight sandstone reservoirs. Field case studies indicate that: (1) the ability of artificial fractures to activate natural fractures and form complex fractures is closely related to net pressure; (2) when the net pressure curve exhibits periodic trends, natural fractures within the reservoir may branch and redirect, forming more complex multi-stage fractures; (3) a higher complex fracture network index post-fracturing corresponds to a higher unimpeded flow capacity, indicating better production enhancement effects. The conclusion suggests that this fracture recognition method can enhance the fracturing potential of fractured tight sandstone reservoirs and is significant for guiding real-time dynamic adjustments in field fracturing operations.